Mitigating Environmental Threats: An Intervention Study on Household Waste Management in Pasirkaliki Village - Ruhmawati, Tati; Wahyudin, Uyu; Sardin, Sardin; Sharaf Eldin Khair, Amar; Shantini, Yanti (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2023)
The lack of awareness regarding the management of household waste, particularly hazardous and toxic waste, poses a significant threat to environmental pollution. This lack of awareness is exacerbated by the accumulation and mixing of such waste with other categories of household waste. This study aims to mitigate the impact of household waste through an assistance mechanism designed to alter waste management behavior. Employing a quasi-experimental method, the research was conducted within the community of Pasirkaliki Village, North Cimahi. The study revealed significant changes in both the knowledge and behavior of the community towards waste management. Post-intervention, there was a notable increase of 16.6% in the community's knowledge compared to pre-intervention measurements. Furthermore, individuals who initially exhibited poor knowledge of waste types showed a remarkable 55.6% increase in understanding. The enhanced knowledge positively correlated with changes in behavior, evidenced by the increased community agreement on sorting waste based on its categories. This behavioral change was attributed to the intervention, supported by a p-value of 0.002. The results underscore the effectiveness of the assistance provided, which involved identifying community tendencies and employing direct involvement to enable individuals to experience the benefits firsthand through education.